High strength tin-based overlay for medium and high speed diesel engine bearing tribological applications. (January 2016) - Zhang, Yi; Tudela, Ignacio; Pal, Madan; Kerr, Ian
Abstract: Tin-based materials are often used as lead-free overlay for half shell bearings in medium and high speed diesel engines for their high resistance to cavitation and corrosion damages and excellent conformability and embeddability for engine tribological applications. Tin-based overlay also offers reasonable fatigue resistance but in order to satisfy the more and more exigent demand of future engine developments especially those fired by natural gases to minimize emissions, a multilayer tin–copper overlay system is herein proposed to overcome the structural weaknesses of traditional monolayer tin–copper overlay therefore provide enhanced tribological performances. Highlights: Multilayer Sn-based overlay for bearing applications in internal combustion engines. Intermetallic compound layer divides overlay into thinner sublayers. Multilayered structure shows superior fatigue, wear and seizure resistance. High performance due to reduced sublayer thickness and sublayer–sublayer interface. Intermetallic compound layer exhibits enhanced frictional properties.